2015
DOI: 10.1093/ageing/afv050
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of EASY-care needs assessment for community-dwelling older people

Abstract: Background: undertaking comprehensive geriatric assessments (CGAs) combined with long-term health and social care management can improve the quality of life of older people [ 1]. The EASY-Care tool is a CGA instrument designed for assessing the physical, mental and social functioning and unmet health and social needs of older people in community settings or primary care. It has also been used as a frailty assessment tool and for gathering population-level data.Objective: to review the evidence of reliability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 20 publications
(40 reference statements)
0
34
0
Order By: Relevance
“…A number of approaches are available to detect the presence of frailty in community-dwelling older adults which are applicable to adults with diabetes [17]. These have been subject to feasibility and validity reviews [18][19][20][21]. A general frailty assessment pathway for people diabetes has recently been described ( Fig.…”
Section: Detecting Frailty In the Community And Development Of An Assmentioning
confidence: 99%
“…A number of approaches are available to detect the presence of frailty in community-dwelling older adults which are applicable to adults with diabetes [17]. These have been subject to feasibility and validity reviews [18][19][20][21]. A general frailty assessment pathway for people diabetes has recently been described ( Fig.…”
Section: Detecting Frailty In the Community And Development Of An Assmentioning
confidence: 99%
“…To date, the instrument has been used in numerous settings and has been completed by healthcare practitioners and older people. It is suggested that completion by nurses is preferable to self‐completion as self‐report may increase risk over or under‐reporting (Craig et al., ). EASYCare is written in clear and simple language which encourages systematic, holistic assessment using a conversational approach.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of intellectual disability from developmental delay, much emphasis was placed on increasing mental activity via socialization (84%) and cognitive stimulation therapy 5 (CST) (72%). The potential reversible causes of cognitive impairment such as polypharmacy, sensory deprivation, and depression were targeted with the recommendations of medication review (41%), ENT referral (28%), and psychotherapy referral (22%).…”
Section: ; 2 ;mentioning
confidence: 99%
“…4 Participants had a greater use of home care and day care resources. 5 The original model was modified to the more streamlined Easy-Care Standard 2010 after early acceptability and reliability trials.…”
mentioning
confidence: 99%